Dementia and memory - Nilsson, Lars-Goran, 1944-; Ohta, Nobuo (Hove, East Sussex : Psychology Press, 2014)
'The aim of this volume is to describe research that is in progress, and the major findings which have been obtained in the scientific study of dementia. With contributions from world-class researchers in this area, the volume offers a concise overview of key findings, and will be of great interest to researchers and advanced students of cognitive psychology, and those working in related fields, such as gerontology, rehabilitation sciences, and allied health'--
'A negative effect of the ageing population is that more individuals are experiencing cognitive decline and some form of neurodegenerative disease. With the number of people experiencing dementia likely to double in the next 20 years, this change in society presents one of greatest challenges facing public health personnel in the 21st century. The aim of this volume is to describe research that is in progress, and the major findings that have been obtained in the scientific study of dementia. Chapters in the first section of the book focus upon early signs of dementia, and consider several approaches to finding early cognitive signs and biological markers of dementia. The second section considers whether dementia is inevitable for people who become very old, and features chapters on risk factors and proactive influences, cognitive reserve and intervention. Each chapter in the final section describes phenomena which are related to differences in function between memory systems, including anterograde memory in fronto-temporal dementia, and the role semantic memory and semantic cognition may play in developing an understanding of the development of the degenerative processes in dementia. With contributions from world-class researchers in the area, this volume offers a concise overview of key findings in recent research on dementia and memory. It will be of great interest to researchers and advanced students of cognitive psychology, and to those working in related fields, such as gerontology, rehabilitation sciences, and allied health'--
Includes bibliographical references and index.
Keywords: Dementia -- Research; Cognitive psychology